The size does matter (2005)
No body refutes the fact that Santiago de Cali has shown for several decades, important problems in its development as an urban and regional center with singular relevance in the country’s territorial organization. This essay pretends to provide important elements to an ongoing debate, about Government assisted housing without detaching it from a more complex issue, as is the creation of a city.